Efforts of the Head of Madrasah in Disciplining Teachers MI Al Ihsan III B Agung Damar Pakamban Daya Pragaan Sumenep - Fauzun Karim, Ahmad; Badriyah, Lailatul (Journal of Islamic Elementary Education, 2024)
An effective madrasa head will certainly affect teacher performance, so that teachers will be more enthusiastic in carrying out their duties and responsibilities as well as their obligations as teachers. This is because the teacher feels that he is getting attention, a sense of security and recognition for his achievements. This study aims to determine the inculcation of discipline in teachers. The aspect studied is the Efforts of the Madrasa Head in Disciplining Teachers MI AL IHSAN III B Agung ‎Damar Pakamban Daya Pragaan Sumenep. In this study the method used is a qualitative method. The subjects of this study were the head of the madrasa and TU. ‎Data collection is carried out through observation, interviews and documentation. The data analysis technique used is data reduction and conclusion. Researchers use source triagulation to obtain data validity. The research results obtained show that the head of the madrasa has tried to discipline teachers at MI AL IHSAN III B Agung Damar Pakamban Daya Pragaan Sumenep. These efforts include: 1. Rule-making is provisions that have been set to regulate a person's behavior in an organization, institution or community group. 2. Teach habits that are taught in madrasas. 3. Punishment means a form of loss and pain that is inflicted on someone who makes mistakes, resistance or violations as a reward or retribution. ‎